MEDIA IDEOLOGICAL REPRESENTATION IN FRAMING THE BAJONESE IN TOROSIAJE VILLAGE, POHUWATO DISTRICT - Hambali, Muhammad; Andarwulan, Trisna; Zulfarina, Prima; Fiaji, Noveria Anggraeni (Jurusan Sastra Indonesia, 2023)
Media can frame differently on the same object. The framing is heavily influenced by the ideology adopted by the media. The purpose of this research is to analyze the representation of media ideology in framing the Bajonese in Torosiaje Village, Pohuwato Regency. The data for this study are in the form of vocabulary, phrases and sentences that reflect ideology in framing the Bajonese from three online mass media, namely kompas.com, mongabay.co.id, and lipunaratif.com. The data collected was analyzed using van Dijk's critical discourse analysis. The framing analysis of the three media was carried out on the aspects of micro structure, super structure and macro structure. The results of the analysis show that the three media analyzed frame the Bajonese differently. Kompas.com frames the Bajonese from the aspect of its uniqueness; mongabay.co.id frames the Bajonese from the aspect of the Bajonese's closeness to nature and the way the Bajonese preserves nature; and lipunaratif.com frame the Bajonese from an economic aspect. Kompas.com and mongabay.co.id rate the Bajonese positively, while lipunaratif.com evaluates the Bajonese negatively. This assessment is related to the desired behavior change by text producers through the framing that is done.